Self-enforcing Norms and the Efficient Non-cooperative Organization of Clans - Kai A. Konrad; Wolfgang Leininger (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
We study how norms can solve distributional conflict inside a clan and the efficient coordination of collective action in a conflict with an external enemy.We characterize a fully non-cooperative equilibrium in a finite game in which a self-enforcing norm coordinates the members on efficient collective action and on a peaceful distribution of the returns of collective action.
Keywords: D72; D74; H41; 330; Free-riding; defence; collective action; distributional conflict; war; norms; Normbefolgung; Gemeinschaft; Verteilungskonflikt; Krieg; Trittbrettfahrerverhalten; Spieltheorie; Normbefolgung; Gemeinschaft; Verteilungskonflikt; Krieg; Trittbrettfahrerverhalten; Spieltheorie